Students' Conceptual Understanding in Science Subjects Using the Macromedia Flash 8 Application with The Instructional Games Model - Afifah, Maghfirah; Yanti Fitria (Jurnal Pendidikan dan Pengajaran, 2024)
This research is motivatedI amlack of use of learning media that is able to facilitate students in the learning process, so that students feel less motivated in reading. The aim of this research is to develop application-assisted learning multimedia Macromedia Flash  8 Model Instructional Games WhichTvalid, practical and effective for improving students' understanding of concepts in science material. The subjects of this research consisted of media experts, material experts, language experts, teachers and students of class V SDN. This research is development research. The model in this research is ADDIE. Based on the results of multimedia researchTThe learning developed is in the valid category both in terms of design, material and language. From the results of practicality tests carried out on students and teachers, multimedia learningTthat was developed is categorized as very practical. Next, based on the test results pretest And post test shows an increase in learning outcomes students by using the developed learning multimedia. Thus, multimedia learning developsNhas been declared valid, practical, and effective for improving students' understanding of concepts in science subjects. This is because the multimedia developed has an attractive design and is easy to operate and the learning material is presented well interesting videos, pictures and animationsTstudents' interest in learning. Using the interactive Macromedia Flash 8 application in the form of instructional games can increase student involvement in the learning process. The visual and dynamic nature of this application allows students to understand abstract concepts in science, such as physics, biology, or chemistry, more easily. Second, the instructional games model facilitates more enjoyable and meaningful learning, which in the end can increase students' learning motivation.